Heterotrophic nitrifying bacteria from activated sludge in DHS reactor for ammonium removal of natural rubber processing wastewater treatment - Minh Duc, Tran; Thi Thanh Thuy, Phan; Thi Huyen, Nguyen; Huong, Nguyen Lan (Vietnam Journal of Science and Technology, 2023)
Two heterotrophic nitrifying bacterial strains, D2 and D7 were isolated from an activated sludge of sponges in a laboratory-scale downflow hanging sponge reactor. Both strains exhibited efficient ammonium removal ability over a wide range of ammonium loads. At the initial concentration of 100 mg/L, NH4+-N was completely degraded within 20 h by both strains. When the initial concentration was increased to 200 mg/L, the NH4+-N removal efficiency was 99.6 % within 20 h by the strain D2 and 61.3 % by the strain D7. In natural rubber processing wastewater, the ammonium removal efficiencies of strain D2 and D7 were 38 % and 99 % with the initial N-NH4+ concentration of 280 and 380 mg/L after 88 h, respectively. The 16S rRNA gene sequence of D2 and D7 showed the highest similarity to the Pseudomonas aeruginosa and Glutamicibacter nicotianae, respectively. This is the first report to demonstrate the ability to remove ammonium in NRPW by ​heterotrophic nitrifying bacteria isolated from activated sludge in DHS reactor.